Perancangan Sistem Informasi Perpustakaan Pada SMK Berbasis Web - Swidayak Simatupang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Currently, technological developments are very rapid. This can be from the use of computers in solving various problems, the progress of information technology provides great opportunities for companies or institutions to implement it as an information system. The library is part of the learning resources that every school must have. Because students can easily find information or knowledge through knowledge through the library. With the development of technology, humans think to be able to work more effectively and efficiently. One of them is to create a computerized system. By utilizing facilities connected to the Internet, the library can be easier in searching for books. The research method used in the library information system at SMK Negeri 1 Sirandorung is a descriptive research method, while for the development of the system using a waterfall which includes a system survey, system analysis, system design, system creation, system implementation. The creation of this application program uses PHP programming and Database Software that uses MySQL support in making reports